FIGURATIVE LANGUAGES USED IN PAULO COELHOS'S NOVEL "THE ALCHEMIST" - Mulyana, Andi Dwi; Mustikawati, Yunitari; Fauzi, Rizki (Journal of English Literature and Linguistic Studies, 2024)
This research is entitled "Figurative Languages Used in Paulo Coelho's Novel 'The Alchemist'." This study aims to analyze the types of figurative language in the novel "The Alchemist" by Paulo Coelho using Perrine's theory (1977). The analysis method used refers to the semantic approach by considering Leech's (1969) theory to explore the meaning in various types of figurative language. The research data were obtained from the extraction of 92 figurative language sentences consisting of simile (24), metaphor (36), personification (27), hyperbole (1), antithesis (2), parallelism (1), idiom (1), metonymy (2), and paradox (1). The analysis also identified two main categories of meaning that are frequently used, namely associative meaning and connotative meaning. The findings provide deep insight into how Coelho utilizes different types of figurative language to enrich the reader's experience and convey profound messages in "The Alchemist". This research is expected to contribute to the understanding of literature and the use of figurative language in modern literary works.